Limitation of fundamental rights in the state of emergency by the COVID-19 pandemic - Gonzales Loli, Martha (2020)
The objective of the investigation was to determine if the limitation of fundamental rights is reasonable, proportional and valid in the State of emergency, taking into consideration that fundamental rights are those superior rights that belong only to human persons established in the Constitution, articles 1 2 and 3; and the State, the State of emergency due to the COVID-19 pandemic, is granted by means of the supreme decree by the President of the Republic, said Supreme Decree is No. 0044-2020-PCM, by means of which the mandatory social isolation ( quarantine), due to the serious circumstances that affect the lives of Peruvian citizens as a result of the COVID-19 outbreak, restricting the exercise of constitutional rights related to personal liberty and security, the inviolability of the home, freedom of assembly and of transit in the national territory of the republic; The investigation was justified because it allows determining whether Supreme Decree No. 0044-2020-PCM is reasonable, proportional and valid to limit fundamental rights in the State of emergency due to the COVID-19 pandemic; The materials used have been the bibliographic sources found in the indexed scientific books and articles, the 1993 Political Constitution of Peru, Supreme Decree 0044-2020-PCM, Resolution No. 1/2020 - Pandemic and Human Rights in the Americas ( Adopted by the IACHR on April 10, 2020); the method used was the deductive method, basic type; The result was that the limitation of fundamental rights in the State of emergency due to the COVID-19 pandemic is reasonable, proportional and valid from the constitutional point of view; and it was concluded that fundamental rights are relative, therefore said fundamental rights may be limited in a State of emergency, respecting the principles of reasonableness and proportionality.